2017
DOI: 10.26444/aaem/74719
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in social capital in relation to self-rated health and subjective well-being in older residents of six regions in Poland

Abstract: The aim of the study was to assess the differences between rural and urban areas as regards the role of social capital and its effect on self-rated health and subjective well-being among older people in Poland. The sample was selected on the basis of multi-stage clustered design from the non-institutionalized adult population. Analysis was based on 1,299 elderly people aged 65 and over from the general Polish population who participated in the COURAGE in Europe project. Six regions of Poland were distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 23 publications
8
52
2
2
Order By: Relevance
“…Once other factors were considered, loneliness was not associated with region or area classification in terms of urban/rural. This lack of an association with urban/rural area classification aligns with the studies from Ireland [36],, Canada [34] and Poland [37] but not from New Zealand, although the basis of their study was service users rather than the general population [36]. Our study reported increased prevalence of loneliness in deprived areas which, whilst not reaching the levels reported by Scarf and de Jong Gierveld [17] of 57%, are significantly higher than those in the least deprived areas (range 36-80% depending on measure and data collection wave).…”
Section: Discussionsupporting
confidence: 87%
“…Once other factors were considered, loneliness was not associated with region or area classification in terms of urban/rural. This lack of an association with urban/rural area classification aligns with the studies from Ireland [36],, Canada [34] and Poland [37] but not from New Zealand, although the basis of their study was service users rather than the general population [36]. Our study reported increased prevalence of loneliness in deprived areas which, whilst not reaching the levels reported by Scarf and de Jong Gierveld [17] of 57%, are significantly higher than those in the least deprived areas (range 36-80% depending on measure and data collection wave).…”
Section: Discussionsupporting
confidence: 87%
“…was not associated with region or area classification in terms of urban/rural. This lack of an association with urban/rural area classification aligns with the studies from Ireland [36] , Canada [34] and Poland [37] but not from New Zealand, although the basis of their study was service users rather than the general population [36]. Our study reported increased rates of loneliness in deprived areas which, whilst not reaching the levels reported by Scarf and de Jong Gierveld [17] of 57%, are significantly higher than those in the least deprived areas (range 36-80% depending on measure and data collection wave).…”
Section: Discussionsupporting
confidence: 87%
“…Havens and Hall (2004) compared loneliness among older (aged 72+) Manitobans using a customised measure (derived from the de Jong Gierveld scale and two single-item questions used elsewhere) ,and reported loneliness prevalence of 47% (rural) and 43% (urban) [35]. A Polish study, reported by Tobiasz-Adamczyk, of 1,200 older adults aged 65+ concluded that there were no differences in loneliness between urban and rural areas using the 3 item UCLA scale (14.7% (urban) versus 15.8% (rural)) [37].…”
Section: The Geography Of Lonelinessmentioning
confidence: 99%
“…Havens and Hall (2004) compared loneliness among older (aged 72+) Manitobans and reported that, using a customised measure (derived from existing de Jong Gierveld scale and two single-item questions used elsewhere), 47% of rural and 43% of urban Manitobans were lonely [33]. A Polish study, reported by Tobiasz-Adamczyk, of 1,200 older adults aged 65+ concluded that there were no differences in loneliness between urban and rural areas using the 3 item UCLA scale (14.7% (urban) versus 15.8% (rural)) [35].…”
Section: Factors Related To Loneliness In Later Lifementioning
confidence: 99%